Implementation of Internal Organizational Communication in the Motor Vehicle Registration and Identification (Regident) System in the South Sulawesi Police Traffic Directorate - Rahmat, Mamat; Kamaruddin, Imran; Unde, Alimuddin; Iqbal, Muhamad; Faried, Muhamad (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
The purpose of this study is to analyze the implementation of organizational communication from the aspect of internal communication in the Motor Vehicle Registration and Identification (Regident) System at the South Sulawesi Regional Police Traffic Directorate. The research uses a quantitative and qualitative approach with an Explanatory Design research design. The results show that internal organizational communication plays a very important role in the context of implementing information technology for the Motor Vehicle Registration and Identification (Regident) System services at the South Sulawesi Regional Police Traffic Directorate. Here are some key points to consider: first, Coordination and Collaboration where internal organizational communication facilitates effective collaboration between various units or departments within the Traffic Directorate. Second is Information Dissemination where effective communication ensures that all staff understand the latest changes or developments in the Regident system, including the implementation of new technology or improvements made. Third is Motivation and Engagement where good communication can increase staff motivation and their engagement in achieving organizational goals, and fourth is Conflict Resolution where open and clear communication helps in addressing conflicts or disagreements among staff or departments that may arise in the management of Regident.